Energy Utilization Efficiency and Entrepreneurial Potential of a Solarbiomass Integrated Drying System - Borah, A.; Sethi, L. N.; Sarkar, S.; Hazarika, K. (Journal of Agricultural Engineering, 2018)
In absence of grid power in most of the production catchments in the North Eastern states ofIndia, coupled with disruptive power situation in areas where it is available, agricultural productsare invariably dried under traditional sun drying. Ginger and turmeric with high intrinsicqualities are two major spices produced in a formidable quantity in the region. Truckloads ofraw ginger are transported to Delhi and other places, causing huge transit losses. A solar-biomassintegrated (IDS) batch drying system was thus designed and developed with a capacity of 100kg/batch. A compound parabolic solar collector coupled with bio-waste fired combustion andheating assembly was designed and attached to a drying chamber consisting of six trays and awind turbine on the top to create the necessary draft controlled by butterfly valves and slidinggates. Thin layer drying experiments were carried out for drying of sliced ginger and turmeric.Fluidized bed dryer (FBD), electrical oven (EO) and open sun drying (OSD) were used forcomparison. Effective moisture diffusivity in case of turmeric drying was nearly 21% more incomparison to ginger drying. Minimum specific energy consumption (SEC) occurred in IDS,and was 14 and 30 times less compared to FBD and OSD, respectively. Considering total heatavailable in the plenum chamber and latent heat of vapourization, the IDS showed 36.33% ofoverall energy utilization efficiency. A run up of 10 years and a break-even of 17.70 % wasestimated, reflecting high entrepreneurial possibility of the developed IDS.